SUMBERDAYAMANUSIAINDONESIA MENGHADAPI ERA GLOBALISASI EKONOMI DITINJAU DARI SEGI PEMERATAAN - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
MostIndonesianswouldagreethattheIndonesianenterprisesshoulddefinitely playamoreefficientroleinthe globaleconomy.However,the argumentthat insistonthequalityofhumanresources.Evenifthegovernmentwas willingto committoacomprehensive programs.                                  .Whileattempttoimprove educationalprogramsthroughinternalrestructuringmay bea validconcept. Thepresent culturein  governmentmeans itis toimplementreformssuccessfully.Thewillingnessandthecapacitytoapproachthecapacityofhumanresourcesforchangetoface_gneconomicalglobalproblems